An exploration of the relationship between nuclear decommissioning projects characteristics and cost performance. (January 2019) - Invernizzi, Diletta Colette; Locatelli, Giorgio; Brookes, Naomi J.
Abstract: Nuclear Decommissioning Projects and Programmes (NDPs) are characterized by high complexity and variety, and a schedule that can take decades. Moreover, NDPs estimates at completion can reach billions of Euro and (for many of these projects) keep increasing, while there is a limited understanding of why this happens. To address this knowledge gap, this paper describes how to statistically test the association between the NDP characteristics and the NDP cost performance. The implementation of statistics on a pool of European NDPs highlights the significance of several country-specific and site-specific characteristics (e.g. respectively, the governance system and the availability of facilities to deal with radioactive material on site). Hence, the original contribution of this paper consists in (i) the selection of statistical tests suitable for analysing small sample sizes (i.e. NDPs) and (ii) the presentation of the results from the implementation of these tests on a pool of 24 European NDPs with an illustrative purpose. Highlights: Nuclear decommissioning projects and programmes often suffer from cost overruns. There is a limited understanding of what causes these cost overruns. The association between project characteristics and performance needs investigation. This paper presents a quantitative approach to statistically test this association. Some country-specific and site-specific characteristics emerge as relevant results.